Biogeographical variability and re-description of an imperfectly known species Hamatocanthoscypha rotundispora (Helotiales, Hyaloscyphaceae) - Kušan, Ivana; Matočec, Neven; Antonić, Oleg; Hairaud, Michel (Phytotaxa, 2014)
Study on fresh collections and type material of Hamatocanthoscypha rotundispora showed that the original description is incomplete and that the variation range in the essential characters is too narrowly defined. In this paper we therefore provide a detailed description, including ascospore morphometry using length, width, length/width ratio and volume. Non-parametric statistics showed significant deviation of normal distribution and high variability of all morphometrical variables, suggesting that use of living material for ascospore morphometrical analysis is more reliable than that of a traditional approach. Geometric criteria for defining the simple spore shape regarding the length/width ratio, polarity and symmetry in straight symmetric spores are proposed. Refractive cytoplasmic globules are described as a new type of inclusions in living cells. Species ecology and biogeography is also discussed.